2020
DOI: 10.4103/jmh.jmh_139_19
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic pattern of postmenopausal women and health issues: A study in rural Bathinda, Punjab

Abstract: Background: The diminishing hormonal concentrations in women after menopause may trap them into a number of reproductive health deficits. Their lifestyle, occupation, dietary constituents, etc., affect the overall health. Unfortunately, women belonging to rural areas lack basic amenities and cultural aspects give them a backseat to pay heed to personal health. Therefore, it is important to take into consideration the demographic profile of rural women. Objective: The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
6
2
Order By: Relevance
“…Senthilvel et al, (2018) 11 too observed same percentage of married women (77.3%) and widows (21.3%) among the postmenopausal women selected for the study. Samtani et al, (2020) 12 showed that more percentage of women (60.2%) having only up to 1-3 children and only 39.3 percent of them had more than 3 children in contrary to our study where only 32.94 percent of the women had 1-2 children and 67.02 percent had 3 or more children. 12 where 94.4 percent of the women were taking vegetarian diet but similar to Tiwari et al, (2020) 13 who found that majority were taking non-vegetarian diet.…”
Section: General Information Socioeconomic Status and Family Details ...contrasting
confidence: 98%
See 1 more Smart Citation
“…Senthilvel et al, (2018) 11 too observed same percentage of married women (77.3%) and widows (21.3%) among the postmenopausal women selected for the study. Samtani et al, (2020) 12 showed that more percentage of women (60.2%) having only up to 1-3 children and only 39.3 percent of them had more than 3 children in contrary to our study where only 32.94 percent of the women had 1-2 children and 67.02 percent had 3 or more children. 12 where 94.4 percent of the women were taking vegetarian diet but similar to Tiwari et al, (2020) 13 who found that majority were taking non-vegetarian diet.…”
Section: General Information Socioeconomic Status and Family Details ...contrasting
confidence: 98%
“…Samtani et al, (2020) 12 showed that more percentage of women (60.2%) having only up to 1-3 children and only 39.3 percent of them had more than 3 children in contrary to our study where only 32.94 percent of the women had 1-2 children and 67.02 percent had 3 or more children. 12 where 94.4 percent of the women were taking vegetarian diet but similar to Tiwari et al, (2020) 13 who found that majority were taking non-vegetarian diet. Around 79 percent of the postmenopausal women were taking 3 meals per day and 20.14 percent were having only two meals in a day.…”
Section: General Information Socioeconomic Status and Family Details ...contrasting
confidence: 98%
“…In a cross-sectional community-based study of 425 women with a high rate of farming jobs (85.2%), Samtani et al found that pesticide exposure induced a later, albeit not statistically significant, age at menopause [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The variables investigated in the studies exploring the influence of work on age at menopause onset were smoking [ 21 , 22 , 23 , 24 ], type of work [ 19 , 21 , 22 , 23 , 24 ], shiftwork [ 25 ], and use of pesticides [ 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation